The Effectiveness of Cucumber (Cucumis Sativus) and Ambon Banana Fruit (Musa Acuminata Cola) in Reducing Blood Pressure in Hypertensive Patients in Palangga Gowa District, Indonesia (Indian Journal of Forensic Medicine & Toxicology, 2021)
Hypertensive patients who are not adhering to treatment cannot control their blood pressure so it is importantto find solutions that can stabilize blood pressure with food that is consumed and can be found anytimearound them. Objective: This study was to identify the effectiveness of cucumber and Ambon banana fruitin reducing blood pressure in hypertensive sufferers. Method: This type of research is a Quasy Experimentwith a non-randomized pretest and posttest control group design. Population of this study were hypertensivepatient in Pallangga subdistrict and Sample participated were 24 people with hypertension selected bypurpossive sampling with the sample formula of unpaired numerical analytic research. Results: There weredifferences before and after treatment in the two groups, there was no difference in the effectiveness of thesample in the two same treatments. Conclusion: Cucumber and banana fruit are effective for lowering bloodpressure.
Keywords: Cucumber juice, Ambon banana fruit, hypertension.